Strengthening National Salt Management Policy Through Synchronization of Central and Regional Government Regulations - Kuswandono, Agung; Yulianda, Fredinan; Taryono, Taryono; Riani, Etty (Unifikasi: Jurnal Ilmu Hukum, 2025)
National salt management in Indonesia is encountering overlapping regulations between the central and regional governments. Therefore, this study aimed to analyze salt management regulations in Indonesia and examine the reinforcement of the national salt management policy through harmonization between central and regional government regulations. The analysis used a normative legal method, focusing on the analysis of positive legal norms regulating the governance of salt sector in Indonesia. The results showed that salt management regulations in Indonesia comprised multiple legal instruments. The analysis further showed that laws primarily prioritized the protection and welfare of farmers, while government regulations permitted imports, leading to the suppression of domestic salt prices. As laws secured a market for locally produced salt, the ministerial regulation facilitated industry access to imported salt. Government regulations predominantly focused on achieving quantitative self-sufficiency targets, and statutory laws prioritized welfare as well as social protection of salt farmers. Regional regulations protected local salt production, and Minister of Trade Regulation advanced industry interests. This study assumed that salt management regulations were available, but there was a regulatory asymmetry between laws and their subordinate regulations. The analysis recommended the development of an incorporated, participatory, and impact-based grand design for a national salt management policy, ensuring social justice in the governance in salt sector of Indonesia.